Wages, Creative Destruction, and Union Networks - Harald Dale-Olsen (Institute of Labor Economics (IZA), 2018)
Do unions promote creative destruction? In this paper we apply a shift-share approach and historical unionisation data from 1918 to study the impact of changes in regional unionisation on regional wage and productivity growth and job creation and destruction during the period 2003-2012. As local regional-industrial unionisation increases, wages grow. Lay-offs through plant closure and shrinking workplaces increase, but entry and new hires are unaffected. Overall, the increased unionisation yields a positive impact on regional productivity, exceeding the wage growth, partly due to the closure of less productive firms, but also enhanced productivity of the survivors and new entrants.
Keywords: J01; J08; J50; J51; 330; trade unions; entry/exit; creative destruction; wages; productivity; historical data